Utilização de técnicas de análise de agrupamento do risco de geada no Estado do Paraná para a cultura do milho safrinha - Martins, Rogério Mendonça [UNESP] (2008)
This work became relevant for verifying the favorable areas for the cultivation of winter corn in the State of Paraná, offering a methodology which led to a better understanding of the agrometeorological variability in the State, providing annual information by decennials, in 22 regions analyzed by a temperature historical data base, diagnosing the homogeneous areas to identify favorable ones for the cultivation of winter corn. To reach this objective, this study adopted the cluster analysis technique through data from IAPAR – Londrina. During the analysis, the agglomerative (bottom-up) hierarchical technique and three clusters methods were used. The historical series were constituted by the nearest neighbor, the farthest neighbor and the non-weighted method to the pairs of arithmetic means. As like the clusters’ synthesis, the nearest and farthest neighbors’ method results showed the development of 4 groups, resulting in 5 groups for the non-weighed method to the pairs of means. The profile graph showed that in all ten simulations there was greater risk of frost in the simulations conducted the latest. Through clustering, locations with the same temperature characteristic were identified, and the simulations provided a basis for best sowing period.